Monitoring, evaluation, and learning: the key to building effective partnerships with government to improve maternal and child health in the Rakai and Kyotera Districts of Uganda - Sklar, Marc; Murokora, Daniel (Frontiers in Public Health, 2024)
This article emphasizes the significance of the Monitoring, Evaluation, and Learning (MEL) system within Babies and Mothers Alive (BAMA) Foundation in building effective sustainable interventions at scale. The foundation aims to enhance the availability of high-quality reproductive, maternal, and newborn care services within the government health sector. The distinguishing characteristic of the MEL system is its integration of organizational learning as a strategic approach to inform the development of dynamic program designs. To do this, it has been necessary to identify crucial requirements through open data exchange with all pertinent stakeholders. This paper demonstrates that our approach to evidence-based learning in a diverse population of locally-based actors and stakeholders, gives voice to the community-based health practitioners and patients that is necessary for transformative maternal health delivery systems. The act of sharing data has presented several possibilities for enhancing current initiatives and extending the reach and scale of our partnership model. We trace the development of the core components of learning and decision making, and reflect on the transition of the program to scale using the LADDERS paradigm. The application of our model of practice has been associated with the increased financially viability and the potential for the sustainable scaling of the program intervention.